Benign Rolandic epilepsy presenting like paradoxical vocal fold motion. (November 2017) - Gross, Jennifer H.; Bertrand, Mary; Hirose, Keiko
Abstract: Paradoxical vocal fold motion (PVFM) is characterized by vocal fold adduction during respiration. Benign Rolandic epilepsy (BRE) is the most common childhood epilepsy and can cause oropharyngolaryngeal or facial manifestations. A 9-year-old male presented with intermittent apnea lasting 30–60 seconds and presumed PVFM. The patient's physical and fiberoptic exam were normal. He was admitted and found to have episodes of oxygen desaturation, neck twitching, and tongue burning. An EEG revealed focal epilepsy. After starting anti-epileptic medications, he had resolution of symptoms. Our patient was eventually diagnosed with BRE, a focal onset epilepsy that can mimic primary otolaryngologic disease.